The Effect of Teachers' Digital Competence and the use of Digital-Based Learning Media on The Effectiveness of Learning in The Classroom - Meilan Matiti; Abd Rahman K. Ma'ruf; Iwan B. Jassin; Sumarni Djafar (Fakultas Ilmu Pendidikan dan Budaya - Universitas Bina Mandiri Gorontalo, 2025)
This research is motivated by the phenomenon of increasing use of technology in education that has not been balanced with teachers' digital competence and optimal use of digital learning media. The purpose of this study is to determine the effect of teachers' digital competence (X1) and the use of digital-based learning media (X2) on the effectiveness of classroom learning (Y). This study uses a quantitative approach with a survey method and data analysis through multiple linear regression. The population in this study were teachers at the elementary school level, with a sampling technique using purposive sampling. The results show that teachers' digital competence (X1) has a significant effect on learning effectiveness (Y), while the use of digital-based learning media (X2) has no significant effect on learning effectiveness. These findings demonstrate the importance of improving teachers' digital competence as a major factor in supporting the effectiveness of classroom learning, rather than relying solely on the use of digital media.